Avaliação do pó do alto-forno como material adsorvente na remoção do corante azul de metileno em soluções aquosas - Chaves, Nayane Oliveira (2021)
Dyes are present in the effluents of many industries such as textile, paper and cosmetics. Adsorption is a widely applied technique for the removal of dyes due to its low cost and excellent efficiency. The use of wastes as alternative low-cost adsorbents has shown promising results. Thus, this work was carried out with the objective of evaluating the use of blast furnace dust as an adsorbent material in the removal of methylene blue dye in aqueous solutions. The blast furnace dust was characterized using laser diffraction granulometry, infrared spectroscopy, X-ray diffractometry, scanning electron microscopy and X-ray energy dispersive spectroscopy, besides the zero point charge determination test. The blast furnace dust was heat treated at 550º C in order to compare the removal efficiency with the untreated blast furnace dust. The parameters evaluated in the adsorption study were the pH, the dosage of the adsorbent, the contact time and the initial concentration of the dye. It was found that the pH did not influence significantly the adsorption process. The results obtained showed that the percentage of dye removal increased with the increase of the adsorbent dosage. The non-calcinated blast furnace dust presented a higher removal efficiency than the calcined blast furnace dust. The maximum adsorption efficiency of 93.68% occurs in 3 hours of contact. The kinetic data were fitted to pseudo-first order, pseudo-second order, Elovich and intraparticle diffusion models. The Elovich model showed the best fit.